Impact of family history of gastric cancer on colorectal neoplasias in young Japanese. (20th December 2012) - Hata, K.; Shinozaki, M.; Toyoshima, O.; Toyoshima, A.; Matsumoto, S.; Saisho, T.; Tsurita, G.
Abstract Aim The aim of this study was to elucidate risk factors for the development of colorectal neoplasia in the young population. In particular, we focused on the family history of gastric cancer. Method Young Japanese subjects aged 30–49 years old who underwent colonoscopy for the first time from August 2007 to August 2008 were included in this study. A total of 300 unselected consecutive patients (mean age 40.5 years) were eligible for analysis, and family history of colorectal cancer and gastric cancer, sex, age, body mass index, positivity of faecal occult blood test and the presence of symptoms were evaluated. Risk factors for developing colorectal adenoma and/or carcinoma were assessed. Results Colorectal neoplasias were detected in 83 (27.7%) cases. Two were found to have invasive carcinoma. Univariate and multivariate analyses revealed that family history of gastric cancer (OR 2.09, 95% CI 1.12–3.92, P = 0.02) was an independent risk factor for the development of colorectal neoplasia, as well as male sex (OR 1.89, 95% CI 1.10–3.27, P = 0.02), older age (OR 2.05, 95% CI 1.18–3.55, P = 0.01) and positive faecal occult blood test (OR 1.99, 95% CI 1.14–3.48, P = 0.02). Conclusion In the young population under 50 years of age, a family history of gastric cancer is an independent risk factor for the development of colorectal neoplasia.